The Influence Of Social Capital On The Productivity Of Lettuce Farmers (Case Study Of Lasinrang Hydroponic Community Pinrang District) - Irmayani, Irmayani; Heru Maizanur; Putera, Ikbal (Jurnal Agricultural Science, 2024)
Hydroponic farming is a promising alternative to increase agricultural productivity and sustainability in Indonesia. In Pinrang district, the Lasinrang hydroponic community has successfully implemented this method, with farmer-to-farmer collaboration, knowledge sharing, and involvement in community activities forming a solid network of mutual support. Despite this success, lettuce farmers still face problems such as lack of effective cultivation knowledge, limited access to quality seeds and fertilizers, and constraints in obtaining profitable markets. Therefore, this study recommends overcoming these problems by strengthening social capital to increase the productivity of lettuce farmers in the Lasinrang Hydroponic community. This study aims to determine the effect of social capital both partially and simultaneously on the productivity of lettuce farmers in Lasinrang hydroponic community, Pinrang Regency. This research uses a quantitative descriptive approach. Data collection techniques using questionnaires, interviews, observation and documentation, while data analysis techniques using multiple linear analysis. The results showed that: (1) the trust variable has no positive effect on the productivity of lettuce farmers (2) the social network variable has no positive effect on the productivity of lettuce farmers (3) the social norm variable has no positive effect on the productivity of lettuce farmers (4) the trust variable, social network, social norms have no positive effect together on the productivity of lettuce farmers.